Crescimento e nutrição de plantas de leucena (Leucaena leucocephala (Lam.) R. de Vit) sob salanidade - de Oliveira Freire, Antonio Lucineudo; Deleo Rodrigues, Teresinha de Jesus [UNESP]; Paes de Miranda, Jose Romilson (Univ Fed Rural Semi-arido-ufersa, 2010)
Excessive salt can to promote water soil retention, reducing your availability to plants. Besides, they can interfere in protoplasm metabolism. The plants ability to survive in salinity conditions is an important factor to geographic distribution and agriculture in salinized regions. The objective of this work was to verify the effects of the NaCl in the growth, dry matter distribution and N, K, Ca, Mg, Na, and Cl content in young plants. The experiment was conducted in 'Leonard' pots, with nutrient solutions, with NaCl ( 0, 25, 50 and 100 mmol L(-1)). Increasing of NaCl concentration reduces growth and total dry matter. There was an increase of N and K content, in shoots, and N and Mg content in roots. There was an reduction in Mg content in shoots, and reduction of Ca content in roots with increasing of NaCl. Leucaena plants were inefficient to exclude Na and Cl, in shoots principally.

O excesso de sais promove a retenção de água no solo, tornando-a cada vez menos acessível às plantas; além disso, íons em excesso podem interferir no metabolismo do protoplasma. A habilidade das plantas em sobreviver sob condições salinas é importante para sua distribuição geográfica e para a agricultura nas regiões salinizadas. Este estudo teve como objetivo verificar os efeitos de doses de NaCl no crescimento, produção de matéria seca e teores de nutrientes em plantas jovens de leucena. O experimento foi conduzido em vasos de ‘Leonard’ com solução nutritiva, contendo 0, 25, 50 e 100 mmol L-1 de NaCl. A salinidade causou redução no crescimento e no acúmulo de matéria seca das plantas. Aumento das doses de cloreto de sódio reduz o crescimento e o acúmulo de matéria seca das plantas de leucena. Ocorre aumento, na parte aérea, nos teores de N e K, e nas raízes, de N e Mg, enquanto há redução nos teores de Mg na parte aérea e de Ca nas raízes, com aumento da dose de NaCl. As plantas de leucena não excluem o Na e o Cl, principalmente da parte aérea.
Growth and mineral nutrition of Leucaena leucocephala (Lam.) R. de Vit) in relation to salinity
Keywords: salinity; Nutrients accumulation; NaCl